Environmental correlates of temporal variation in the prey species of Australian fur seals inferred from scat analysis. Issue 10 (5th October 2022) - Kliska, Kimberley; McIntosh, Rebecca R.; Jonsen, Ian; Hume, Fiona; Dann, Peter; Kirkwood, Roger; Harcourt, Robert
Abstract : Marine ecosystems in southeastern Australia are responding rapidly to climate change. We monitored the diet of the Australian fur seal ( Arctocephalus pusillus doriferus ), a key marine predator, over 17 years (1998–2014) to examine temporal changes. Frequency of occurrence (FO) of prey was used as a proxy for ecosystem change. Hard part analysis identified 71 prey taxa, with eight dominant taxa in greater than 70% of samples and predominantly included benthic and small pelagic fish. FO changed over time, e.g. redbait ( Emmelichthys nitidus ) reduced after 2005 when jack mackerel ( Trachurus declivis ) increased, and pilchard ( Sardinops sajax ) increased after 2009. Using generalized additive models, correlations between FO and environmental variables were evident at both the local (e.g. wind, sea surface temperature (SST)) and regional (e.g. El Niño–Southern Oscillation Index (SOI), Southern Annular Mode (SAM)) scales, with redbait and pilchard showing the best model fits (greater than 75% deviance explained). Positive SAM was correlated to FO for both species, and wind and season were important for redbait, while SOI and SST were important for pilchard. Both large-scale and regional processes influenced prey taxa in variable ways. We predict that the diverse and adaptable diet of the Australian fur seal will be advantageous in a rapidly changing ecosystem.